Coplanar Waveguide Fed Compact Wide Circular-Slotted Antenna for Wi-Fi/WiMAX Applications. (25th February 2014) - Samsuzzaman, M.; Islam, T.; Abd Rahman, N. H.; Faruque, M. R. I.; Mandeep, J. S.
Abstract : A coplanar waveguide (CPW) fed printing and wide circular slotted, dual band antenna for Wi-Fi/WiMAX applications are presented. The antenna mainly encompasses a ground with a wide circular slot in the centre, a rectangular feeding strip, and two pairs of symmetric planar inverted L (SPIL) strips connecting with the slotted ground. The tuning effects of the rectangular patch, ground size, and SPIL strips to the resonance and matching condition are examined by HFSS and the prototype is fabricated and measured. The simulation and experimental results show that the antenna has an impedance bandwidth with −10 dB reflection coefficients 600 MHz (3.26–3.86 GHz, lower band) and 1040 MHz (5.02–6.26 GHz, upper band), which can cover both the Wi-Fi 5.2/5.5/5.8 GHz and WiMAX 3.3/3.5/3.7/5.8 GHz bands. Moreover, a stable omnidirectional radiation pattern and average peak gain for lower band 3.23 dB and upper band 5.93 dB have been achieved, respectively.